Analysis of Factors Contributing to Low Bed Occupancy Rate in Inpatient Wards - Paloma, Ira; Maryana, Maryana; Nurvinanda, Rezka (Inspirasi Foundation, 2025)
Introduction: The Bed Occupancy Rate (BOR) is an important indicator in assessing the efficiency of hospital bed utilization. A low BOR can reflect poor service quality and impact hospital revenue. Objective: This study aims to analyze the factors causing the low BOR in inpatient wards of Sejiran Setason Regional General Hospital in 2025 based on the 5M management approach (Man, Material, Method, Machine, and Money). Method: This study used a qualitative design with a phenomenological approach. The research informants consisted of primary, supporting, and key informants selected purposively. Data collection techniques included in-depth interviews, observation, documentation, and focus group discussions (FGDs). Data analysis employed the Miles and Huberman technique, which encompassed data reduction, data presentation, and conclusion drawing. Result: The results indicate that the low BOR is caused by a shortage of healthcare workers, limited facilities and infrastructure, suboptimal service flow, underutilization of information systems, and budget constraints. Furthermore, external factors such as transportation access, socioeconomic conditions, and community preferences also contribute. Conclusion: The study concluded that the low BOR is influenced by a combination of internal and external factors. It is recommended that hospitals conduct a comprehensive evaluation of their service management systems, improve resources and facilities, and strengthen public education and promotion strategies to increase patient trust and visits.